The usage of technology among education students in University Utara Malaysia: An application of extended technology acceptance model - Raman, Arumugam (2011)
This paper reports the findings of perceived usefulness and perceived ease of use on the extent of computer usage among a group of full time Bachelor of Education undergraduates at the College of Arts and Sciences, University Utara Malaysia.This study is based on Technology Acceptance Model (TAM) and also looks at the moderating role of gender in the above relationship questionnaires were used to collect data.A total of 120 students responded to the survey.Results from the study shows that perceived usefulness (ß=0.29, p<0.01), perceived ease of use (ß=0.25, p<0.01), and subjective norm was (ß=0.15, p<0.05) were positively related to computer usage.The findings also revealed that gender was not a moderator in the mentioned relationship but can be considered as significant independent predictor of usage.Male students exhibited higher usage of the computer compared to the female students.